Variation in total lipid content and fatty acid composition in the muscle of Bombayduck Harpodon nehereus (Hamilton, 1922) with respect to size and season - Rathod, Ramesh; Pal, Asim K; Chakraborty, Sushanta K; Gudipati, Venkateshwarlu (Indian Journal of Fisheries, 2013)
In view of the increased importance of fish lipids owing to their human health beneficial effects, the total lipid content and fatty acid composition in the muscle of Bombayduck (Harpodon nehereus) of different sizes harvested in different seasons were studied. Among the three seasons studied, total muscle lipids were significantly (p<0.05) high during winter and low in monsoon season. In all the seasons, the increased lipid levels were noticed with increase in size. A significant variation in total lipid was observed with the lowest level (1.65 %) in small sized Bombayduck of monsoon season and the highest level (4.68 %) was observed in large sized fish caught in winter season. A total of 37 fatty acids encompassing n-3, n-5, n-6, n-7, n-9 and odd and branched chain fatty acids were characterised with relatively high levels (26.57 – 35.03%) of n-3 polyunsaturated fatty acids (PUFA) and a favourable ratio (3 to 4.69) of n-3/n-6 PUFA demonstrating excellent nutritional quality of Bombayduck. Though the fatty acid composition was not influenced by the size of fish, the effect of season on fatty acid composition of Bombayduck was clearly established by principal component analysis.